Regional head election, money politics, and corruption: an alternative solution / Effendi Hasan M.A … [et al.] - Hasan M.A, Effendi, Ubaidillah, Muliawati, Helmi, Nofriadi (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
This study aimed to study the massive and systematic extent of money politics in the 2017 elections of the Bireuen District. This study used a qualitative method with the participant-observer approach. Data were collected through FGD at Al-Muslim University in Bireuen and in-depth interviews with the relevant parties. The practice of money-politics in the Bireuen election was very immaculate and well-coordinated. It started with the collection of the photocopies of ID and family registry cards and ended with the distribution of money before and after the voting. The campaign teams in each village helped to assist this process to the villagers. The study found five major causes of money politics in the Bireuen District. First, the public confidence in the political elections has declined. Second, the political orientation of the community was pragmatic. Third, several candidates had the same power in the election; thus, they had no other choices but to give away money to the public in the hope of being elected. Fourth, the prevention of money politics in the local elections of the Bireuen regent was somewhat weak. The elections supervisory committee does not have the authority to punish the political money perpetrators but can only give recommendations to the District Independent Elections Commission (KIP). These recommendations are subject to being processed or neglected. Lastly, the regulation of money politics was also weak in the Bireuen regional election. This massive money politics in Bireuen can be prevented by establishing a concept and formulating policies in the form of qanun (Islamic bylaws) in Aceh. The qanun could cancel or disqualify the regent candidates if they are proven to have committed money politics based on convincing and legally binding evidence. The political parties could also be deprived of their political rights to carry the regional head candidates fo r a term of office. Aceh, through its self-government, has a special authority to produce regulations that do not contradict the higher regulation in Indonesia. The function of the qanun is to break the chain and the money politics system by imposing punishment to the regent candidates and political parties. This research has never been investigated before, especially the potential of regulation to break the chains of money politics by establishing a qanun to be applied in Aceh.